Inhalational injury and use of heparin & N-acetylcysteine nebulization: A case report - Nissar Shaikh (11659441) (2022)
Inhalational injury to the upper and lower airway occurs due to thermal or chemical irritation causing airway edema, capillary leak, mucin, and fibrin debris forming clots and soot. The use of unfractionated heparin (UFH) nebulization was found to be effective by dissolving airway clots. We report a case of inhalational burn injury where UFH nebulization led to a better outcome. A healthy male was trapped in a residential room during a fire in the building. He sustained facial, neck, upper chest, and left upper extremity burns accounting for 25% of body surface area. He was intubated at the site and started on supportive care. In the surgical intensive care unit, bronchoscopy showed severe tracheobronchial burn injury; a thorough lavage was done, started on UFH and N-acetylcysteine nebulization (NAC). The patient improved, and his trachea was extubated on day 6. In our patient, unfractionated heparin nebulization was beneficial as the patient was extubated early without landing to acute respiratory distress syndrome. Other Information Published in: Respiratory Medicine Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rmcr.2022.101640